THE TAXATION OF ILLEGAL RECEIPTS: A PYRAMID OF PROBLEMS! A discussion on ITC 1789 (Income Tax Court – Natal) - Elzette Muller (Obiter, 2022)
The question whether or not income which is received by a taxpayer in the course of carrying on illegal activities should be regarded as being received by or accrued to such taxpayer for purposes of assessing such person’s gross income has been an object of debate, both in South Africa and abroad. A recent case on this topic, ITC 1789 (67 SATC 205), which will be discussed hereunder, once again highlighted the uncertain treatment of illegal income for purposes of income tax. The case concerned the inclusion of proceeds from a pyramid scheme, deposits as well as commissions, as gross income in the hands of the scheme perpetrators. Although this discussion will focus on the said case, the history of cases that have dealt with the concept of “beneficial receipt” will be set out to provide a clear understanding of how the law has been applied and will set the background for determining whether or not the case under discussion has been correctly decided. It will be shown that the root of the problem, in the cases that dealt with illegal receipts, is the inconsistent application of various approaches to the meaning of “beneficial receipt”. The courts have followed an objective approach in some cases, and a subjective approach in others. This discussion will show that, by consistently applying the subjective approach of paying regard to the intention of the taxpayer for purposes of “beneficial receipt”, the current confusion can be rectified. It should be noted that, although the treatment of illegal income involves both the inclusion of illegal income as part of gross income as well as the deductibility of expenses incurred in the carrying on of illegal activities, the case under discussion only dealt with the issue of the inclusion of illegal income. This discussion will be limited to the first issue and will not deal with the deductibility of expenses incurred as part of illegal operations.